Neuro-psychiatric manifestations in patients with systemic lupus erythematosus: A systematic review and results from the Swiss lupus cohort study. (September 2021) - Meier, Aline L; Bodmer, Nicolas S; Wirth, Carla; Bachmann, Lucas M; Ribi, Camillo; Pröbstel, Anne-Katrin; Waeber, David; Jelcic, Ilijas; Steiner, Urs C; ,
Objectives: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease associated with neuro-psychiatric (NP) manifestations. Frequency and patterns of neuro-psychiatric systemic lupus erythematosus (NPSLE) vary substantially between patients. We conducted a systematic review (SR) of the literature and examined prevalence and characteristics of NPSLE in the Swiss SLE cohort study (SSCS). Methods: The SR search was performed between January 1999 and January 2020. We included prospective/cross-sectional studies focusing on NPSLE. We secured study characteristics, cohort compositions and frequencies of NP manifestations, assessed heterogeneity across reports and investigated sources of variation using meta-regression models. Regarding the SSCS, we reviewed all patients included and classified NP manifestations. Results: The SR searches identified 530 studies. We included 22 studies in our meta-analysis, the mean frequency of NPSLE ranged from 10.6% to 96.4%. The frequency of NPSLE in the SSCS was 28.1%. Severe events including cerebrovascular insults, seizures and psychosis appeared in 7.1%, 5.3% and 6.5% respectively. There was a linear relationship between duration of SLE and cumulative incidence of NPSLE. Conclusions: The spectrum of NPSLE is very broad. The diagnostic work-up and rates of reported manifestations varied substantially across studies. We call for concerted efforts and consensus regarding definitions of NPSLE that will facilitate accurate diagnosis and attribution to SLE, particularly with a view to timely intervention and patient outcomes.